Analysis of the Development of the Tangkahan Tourism Area - Muhammad Yusuf Nasution; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to examine the Analysis of the Development of the Tangkahan Tourism Area. This type of research uses qualitative descriptive research. The data collection techniques in this study are interviews and observations. Data collection is data obtained from research sources that are still raw and have not been processed by researchers Data reduction, data presentation, the process of drawing conclusions involves the researcher interpreting the data that has been displayed. The methods carried out include comparisons, grouping, making patterns, and triangulating. The results of tourism development research are carried out with the aim of making tourism advanced and developing in a better direction in terms of the quality of facilities, facilitating access anywhere, becoming a desired destination, and making good economic benefits for the surrounding community. Tourism planning and development is not a stand-alone system, but is closely related to other development planning systems intra-sectoral and intra-regional. Then the development of tourist destinations requires good and appropriate planning techniques. The development technique must combine several aspects to support the success of tourism. These aspects are accessibility aspects (transportation and marketing channels), characteristics of tourism infrastructure, level of social interaction, linkage/compatibility with other sectors, resilience to tourism impacts, level of resistance of local communities, and so on.